Colonic capacitance and transit in man: modulation by luminal contents and drugs. Issue 4 (April 1990) - Kamath, P S; Phillips, S F; O'Connor, M K; Brown, M L; Zinsmeister, A R
Abstract : We have examined whether the human colon is able to adapt its capacity to receive fluid, specifically, whether the caecum and ascending colon ('right colon') exhibited any reservoir function. Healthy volunteers had the caecum intubated from above with a device that permitted intraluminal pressures to be recorded while fluids were instilled into the caecum. Perfusates contained 99mTc-DTPA (diethylenetriamine pentaacetic acid) and volumes of the right colon were determined by two plane scintigraphy using gamma cameras. Different individuals received caecal infusions of 154 mM NaC1 (saline), an emulsion of oleic acid (with bile acids and lecithin) or a 100 mM solution of mixed short chain fatty acids. Each person was pretreated by intravenous saline (placebo), morphine sulphate (100 micrograms/kg) or naloxone (5.5 mg as a bolus, followed by 10 micrograms/kg/min). Volumes of the right colon were smallest during oleic acid infusion; morphine reversed the effect of luminal fat and allowed the colon to accommodate larger volumes. Transit from the right colon was more rapid for the emulsion of oleic acid than it was for saline or solutions of mixed short chain fatty acids. We conclude that the right colon may act as a reservoir and that this function can be modified by the nature of the contents and by pharmacological agents.